ASUHAN KEPERAWATAN TERAPI MADU PADA BALITA DIARE DI RS HARAPAN BUNDA BATAM - Nursahida Rifqah; Ditte Ayu Suntara (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Diarrhea is one of the most common health problems in toddlers, characterized by three or more loose or watery bowel movements per day and, if left untreated, may rapidly lead to dehydration, electrolyte imbalance, and impaired growth. Honey has antimicrobial, anti-inflammatory, and prebiotic properties that are reported to help reduce the frequency of diarrhea. This study aimed to describe nursing care for a toddler with diarrhea through the application of honey therapy at Harapan Bunda Hospital, Batam, in 2025. A descriptive case-study design was used, applying the nursing process (assessment, diagnosis, intervention, implementation, and evaluation) to one toddler over four days of care. The assessment found a defecation frequency of more than five times per day, dry oral mucosa, and perianal excoriation, leading to three nursing diagnoses: diarrhea, hypovolemia, and impaired skin integrity. Honey therapy, given orally three times daily (5 mL each time) for four consecutive days, was followed by a decrease in defecation frequency, improved mucosal hydration, and healing of the perianal irritation. Honey therapy can be considered an effective, low-cost, non-pharmacological complementary intervention to support the management of diarrhea in toddlers.Keywords: Diarrhea, Toddler, Honey Therapy, Nursing Care.